Rising US LNG exports and global natural gas price convergence - Robert Ialenti (Bank of Canada, 2021)
We assess how rising exports of US liquefied natural gas (LNG) affect the convergence of natural gas prices worldwide. Using standard principal component analysis and cointegrating techniques, we show that the degree of co-movement between global benchmark prices for natural gas has strengthened since the United States began the large-scale export of LNG in 2016. At the same time, we find that global natural gas prices do not yet adhere to the relative law of one price. Our results also suggest that issues related to storage access in Alberta between 2017 and 2019 have limited price co-movements between major benchmarks for natural gas in the United States and Canada. In addition, we use vector error correction models to show that natural gas prices in Europe and Asia respond negatively to increased exports of US LNG. These results may have implications for the development of future LNG export capacity in Canada.
Keywords: C32; F15; K41; L95; 330; International topics; Market structure and pricing